Comparative Performance Study on Symmetric and Asymmetric Encryption Algorithm: Comprehensive Report of a Comparative Study (Comprehensive Journal of Science, 2026)
The boom in the digital communication, e-commerce and cloud-based systems has highlighted the nature of cryptographic systems in the ensuring of security in information exchange. Symmetric and asymmetric encryption algorithms belong to the most studied cryptographic paradigms and the building blocks of the existing security systems. Although both types provide the same degree of confidentiality the performance features of the two types and their actual performance is very different. The present paper will provide a comparison of the two kinds of algorithms with a focus on the computational speed, memory requirement, scalability, and attack resistance. The experimental findings and literature have demonstrated that the symmetry algorithms such as Advanced Encryption Standard (AES) is more efficient and quick in its simultaneous performance and must be applied in the case of encrypting huge amounts of information. On the other hand, asymmetric algorithms, including the Rivest Shamir Adleman (RSA) and Elliptic Curve Cryptography (ECC) are computationally inefficient, yet offer advantages in distributing keys, as well as authentication. These findings are the reason why there is an ever-growing tendency to consider hybrid cryptosystems incorporating the strengths of both approaches to reach an equilibrium of performance and security (Stallings, 2017; Singh and Kumar, 2020).
Keywords: Symmetric encryption, Asymmetric encryption, Performance evaluation, AES, RSA, ECC, Cryptography